2005
DOI: 10.1007/s00705-005-0515-z
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a coding region for the helper component-proteinase in the genome of cucumber vein yellowing virus, a whitefly-transmitted member of the Potyviridae

Abstract: The complete nucleotide sequence of isolates of Cucumber vein yellowing virus (CVYV) has been determined. The viral genome comprises 9734 nucleotides, excluding a 3'-terminal poly(A) sequence. The genome of CVYV has a 5'-non coding and a 3' non coding region of respectively 67 and 240 nucleotides. The RNA of CVYV encodes a single polyprotein of 3148 amino acid residues and has a deduced genome organization and motifs typical for a member of the family Potyviridae. However, CVYV is atypical because it lacks a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 28 publications
0
59
0
Order By: Relevance
“…Primers 7-CVYV and VYVC-1667rev were used in one of the reactions to amplify a fragment including CVYV nt 7 to 1667 (numbering is according to the sequence published by Janssen et al [20]). This fragment was cloned into pCRII by the TOPO cloning system (Invitrogen) to create pCRII-5ЈP1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers 7-CVYV and VYVC-1667rev were used in one of the reactions to amplify a fragment including CVYV nt 7 to 1667 (numbering is according to the sequence published by Janssen et al [20]). This fragment was cloned into pCRII by the TOPO cloning system (Invitrogen) to create pCRII-5ЈP1.…”
Section: Methodsmentioning
confidence: 99%
“…However, CVYV differed from another ipomovirus, Sweet potato mild mottle virus (SPMMV) and from the remaining sequenced monopartite members of the family Potyviridae, in that it lacks a sequence coding for a putative HCPro. CVYV showed an exceptionally large P1 protein, with a C-terminal serine protease domain similar to those of the P1s of members of the genus Potyvirus (20). The putative cleavage site separating CVYV P1 and P3 was also similar to the P1-HCPro junction of potyviruses.…”
mentioning
confidence: 91%
“…However, the sequence encoding this protein is absent from the genome of some members of the Ipomovirus genus, such as Cucumber vein yellowing virus (CVYV), Squash vein yellowing virus (SqVYV), and Cassava brown streak virus (CBSV) (Janssen et al 2005;Li et al 2008;Mbanzibwa et al 2009). Whereas in typical potyviruses the 59 terminal region of the genome codes for a single serine proteinase (P1), the 59 terminal region of the genome of CVYV and SqVYV codes for two similar serine proteinases arranged in tandem (P1a and P1b), and the P1b has been shown to have RNA silencing suppression activity (Valli et al 2006;Li et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This family consists of five genera with monopartite plus-strand RNA genomes, namely, Potyvirus, Rymovirus, Macluravirus, Ipomovirus, and Tritimovirus, and the genus Bymovirus, which has a bipartite genome (41). It was recently reported that the ipomovirus Cucumber vein yellowing virus (CVYV), which lacks HCPro (32), has a duplicated P1 coding sequence, and the downstream P1 copy, P1b, is a second RNA silencing suppressor in the Potyviridae family (76). In silico analysis suggested that both P1 copies, P1a and P1b, are serine proteinases (75), and the enzymatic activity of P1a was verified experimentally (76).…”
mentioning
confidence: 99%